Aplicación del sistema de costos por Actividades y su efecto en la rentabilidad de la 'empresa Cementos selva S.A. - Coronel Cotrina, Cesar Orlando (2014)
In a globalized world and in the now, the global capital markets, business relations, the competitiveness of enterprises, massive selling products and aggressive advertising campaigns, among other activities, have no borders. Investors. and directors of companies that operate in these scenarios, do not expect to have barriers to develop its business activities anywhere in the world and aspire to have access to financial information of high quality, reliable, transparent and comparable, as the basis for making the best business decisions. This, as a result of the opening of new markets and internationalization of the economy that are imposing totally unknown conditions. The concern arises when entrepreneurs find that nothing is under your control. If the market was previously a seller's market, you can ensure that it is now a buyer's market; a market where customers who impose conditions to buy are. So if the new market approaches are the ones who will set the price, this will be at least discretionary formula of financial profitability, employers only have left, as an element of cost control. Those entities not anticipate making changes requires a competitive environment will not be able to survive financially. So the owners, shareholders and employees of businesses should opt for techniques and tools for better decision-making to facilitate the measurement of financial indicators to present the economic reality of the company. A practical tool for this is the implementation of a System Costs Activities which aims to obtain high quality information and allows the accounting area preparation, presentation and use of financial statements of general purpose reliable, transparent and comparable